2010
DOI: 10.1016/j.ecl.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Status: Definition, Prevalence, Consequences, and Correction

Abstract: Vitamin D is obtained from cutaneous production when 7-dehydrocholesterol is converted to vitamin D3 (cholecalciferol) by ultraviolet B radiation or by oral intake of vitamin D2 (ergocalciferol) and D3. An individual's vitamin D status is best evaluated by measuring the circulating 25-hydroxyvitamin D [25(OH)D] concentration. Though controversy surrounds the definition of low vitamin D status, there is increasing agreement that the optimal circulating 25(OH)D level should be ~30-32 ng/ml or above. Using this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
1
27

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(147 citation statements)
references
References 117 publications
5
112
1
27
Order By: Relevance
“…Vitamin D insufficiency/deficiency has been considered a public health problem worldwide because of its implications in the bone tissue, as well as in maintaining the normal homeostasis of Ca and P which is already well known (1)(2)(3) . In tropical countries this insufficiency/ deficiency has not been cited as a major concern, since cutaneous synthesis from sun exposure is the major source of vitamin D in most individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D insufficiency/deficiency has been considered a public health problem worldwide because of its implications in the bone tissue, as well as in maintaining the normal homeostasis of Ca and P which is already well known (1)(2)(3) . In tropical countries this insufficiency/ deficiency has not been cited as a major concern, since cutaneous synthesis from sun exposure is the major source of vitamin D in most individuals.…”
mentioning
confidence: 99%
“…An adequate vitamin D level is essential in all stages of life, and there is consensus that the best status indicator of this vitamin is the serum concentration of calcidiol (25(OH)D) (3) . Low levels of calcidiol directly affect Ca absorption and bone mineralization.…”
mentioning
confidence: 99%
“…Initial studies [36][37][38] found that, as renal insufficiency progresses, vitamin D 2 supplementation led to less reduction in serum PTH. Patients with CKD stage 3 benefited more from VitD supplements, than those with CKD stage 4 and those on maintenance hemodialysis (HD).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Cholecalciferol therapy leads to upregulation of VitD response genes in monocytes of patients on maintenance HD, indicating that oral VitD preparations have a biologic effect on circulating monocytes and associated inflammatory markers in HD patients [33,36,49].…”
Section: Mechanism Of Pth Decrease With Vitd Supplementationsmentioning
confidence: 99%
“…The correlation between low serum levels of vitamin D and decrease in insulin sensitivity has been reported in recent crosssectional investigations (11)(12)(13). Several epidemiological and cross-sectional investigations have detected that low levels of 25 (OH) D in circulation are related to increase of fasting blood sugar, insulin and higher prevalence of diabetes (14,15).…”
Section: Introductionmentioning
confidence: 99%